Investigating the effectiveness of reality therapy, behavioral flexibility and aggression of spouses of people with a history of drug abuse in addiction treatment centers between the ages of 40-30 (Scientific Journal of Research Studies in Future Psychology, 2024)
This  study aimed to stuy the effectiveness the reality therapy on hypertension, functional flexibility and aggression of spouses of people with a addition of substance abuse  Residence centers. research on semi-experimental  project and  statistical population  of the study  included  the spouses of people with a history of substance  abuse in addiction  treatment centers between  the ages of  40-40,whose spouses lived in addiction  treatment centers in shiraz in 1399.to conduct  research, 30 spouses of people with a history of substance abuse in selected  addiction treatment  in shiraz all selected, who are randomly assigned to two experimental  and control groups. the two groups were matched  in terms of demographic  characteristics. the research measurement  tools were HS synder  (HS),aggression  Qutstionnaire (AGQ)and flexibility  Qutstionnaire (CFI).the results  of data analysis using one-variable  and multivariate  analysis  of variance  showed that reality therapy  had a significant effect  on the well-being  of spouses of  people with a history  substance abuse in addiction  treatment centers  the ages of 40-40  reality  therapy  also had a  significant effect  on the functional  flexibility of the  spouses  of people with a history  of substance abuse in addiction  treatment centers between  the ages of 40 and 30. according to other results  of reality therapy, the aggression of the  spouses of people with a history of substance  abuse in addiction treatment  centers between the ages  of  40 and  30 had a significant effect.